The invasive mosquito species Aedes albopictus: current knowledge and future perspectives - Bonizzoni, Mariangela; Gasperi, Giuliano; Chen, Xioaguang; James, Anthony A. (Trends in parasitology, 2013)
•The Asian tiger mosquito Aedes albopictus is currently the most invasive vector species worldwide.•Aedes albopictus are competent vectors for different arboviruses, including Dengue and Chikungunya viruses.•The public health relevance of this species is increasing in geographic extent and the number of people affected.•We present a brief summary of our current knowledge of the biology, ecology, vector competence, and vector control strategies.•Future research perspectives on this species were derived from a panel discussion among worldwide experts. One of the most dynamic events in public health is being mediated by the global spread of the invasive mosquito Aedes albopictus. Its rapid expansion and vectorial capacity for various arboviruses affect an increasingly larger proportion of the world population. Responses to the challenges of controlling this vector are expected to be enhanced by an increased knowledge of its biology, ecology, and vector competence. Details of population genetics and structure will allow following, and possibly predicting, the geographical and temporal dynamics of its expansion, and will inform the practical operations of control programs. Experts are now coming together to describe the history, characterize the present circumstances, and collaborate on future efforts to understand and mitigate this emerging public health threat.